Digitalisation in 21st century music education: Smartphone as communication and teaching learning tool / Havilah Ginajil - Havilah , Ginajil (2020)
Parents were the biggest influencer to every child’s development in any area of life, thus it is crucial to enhance parental involvement in order to assist efficiently in child’s learning at home environment. Moreover, this generation of children has commitment in more than one activity every week, therefore it is important for parents to manage the time equally in turn to have quality performances achieved from the children. Thus, this study is conducted on Digitalisationin 21st Century Music Education: Smartphone as Communication and Teaching-Learning Tool. The aims of this study are: (1) to investigate the effectiveness of digital device in enhancing parental involvement in children’s musical learning; (2) to identify the function of digital devices in improving communication among parents, music teachers and music students; and (3) to examine how digital device can be an effective teaching and learning tools. A total of 12 participants (4 parents, 4 music teachers and 4 music students) were purposefully selected according to the criteria needed in this study. In addition, 30 minutes face-to-face in-depth interview with semi-structured and open-ended questions was conducted with the individuals. The results found that digital device as smartphone was a useful tool to enhance communication between parent, teacher and student, also to access information efficiently through fingertips. Although smartphone benefits each individual in various ways, it should not replace the notion of parental involvement and face-to-face interaction between home and school partnership.